Occupational stress among nursing technicians and assistants: coping focused on the problem - Bastos Teixeira, Carla Araújo; de Souza Pereira, Sandra; Cardoso, Lucilene; Seleghim, Maycon Rogério; Naves dos Reis, Leonardo; da Silva Gherardi-Dona, Edilaine Cristina (Investigación y Educación en Enfermería, 2015)
Objective. To analyze the association between strategies used to cope with occupational stress that are focused on the problem wand the personal characteristics of nursing technicians and assistants. Methods. This quantitative and correlational study was conducted in a large teaching hospital in the São Paulo State, Brazil, in 2013. A randomized sample with 310 participants (198 nursing assistants and 112 nursing technicians) comprised the study population. Data were collected using a sociodemographic characteristics questionnaire and Scale of Ways of Coping with Problems. Data were submitted to univariate analysis, and variables with statistical significance (p<0.20) were submitted posteriorly in a multiple regression model. Results. Most employees were women (76.1%) older than 40 years (67.7%), had nine to 11 years of formal education (73.5%), had a partner (58.7%), were Catholic (53.2%), and had children (74.5%). The final multiple regression model consisted of variable years of formal education and number of children. Conclusion. In this study, formal education and number of children were more strongly associated with a greater use of coping strategies focused on the problem. Such a strategy is related to minimal vulnerability to stress related to the working environment. How to cite this article: Teixeira CAB, Pereira SS, Cardoso L, Seleghim MR, Reis LN, Gherardi-Donato ECSG. Occupational stress among nursing technicians and assistants: coping focused on the problem. Invest Educ Enferm. 2015; 33(1):